2018
DOI: 10.1016/j.bbadis.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic modeling helps interpret transcriptomic changes during malaria

Abstract: Disease represents a specific case of malfunctioning within a complex system. Whereas it is often feasible to observe and possibly treat the symptoms of a disease, it is much more challenging to identify and characterize its molecular root causes. Even in infectious diseases that are caused by a known parasite, it is often impossible to pinpoint exactly which molecular profiles of components or processes are directly or indirectly altered. However, a deep understanding of such profiles is a prerequisite for ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Metabolic flux models are particularly helpful for these such joint analyses, as they can combine transcriptional data (which is annotated and thus of known origin) with metabolomics data (from unknown origin). Putting these data together can help to illustrate the predicted activity of various metabolic pathways of either the host or parasite (Chiappino-Pepe et al, 2017;Tang et al, 2018).…”
Section: Data Wrangling: Bioinformatics Approaches For Tackling the Mmentioning
confidence: 99%
“…Metabolic flux models are particularly helpful for these such joint analyses, as they can combine transcriptional data (which is annotated and thus of known origin) with metabolomics data (from unknown origin). Putting these data together can help to illustrate the predicted activity of various metabolic pathways of either the host or parasite (Chiappino-Pepe et al, 2017;Tang et al, 2018).…”
Section: Data Wrangling: Bioinformatics Approaches For Tackling the Mmentioning
confidence: 99%
“…Malaria systems biology in its most ideal form would include the development of predictive mathematical models that both codify and enhance our understanding of the disease. Beyond the well-trodden field of mathematical modeling of population-scale disease transmission, modeling approaches have also been used to gain greater insights into, for example, the timing of anemia compensation during the course of Plasmodium infection [96], the timing of parasite infection and release before parasitemia can be detected by current methods [5,55], and how models of metabolic pathways may be used to interpret transcriptomic datasets [97]. Efforts like these range from focused models to fit only a few types of physiological measurements to broader pathway-level models, and they have provided noteworthy insight.…”
Section: Discussionmentioning
confidence: 99%
“…Considered by themselves and focusing solely on genes coding for specific enzymes of purine metabolism, the findings showed patterns that did not make sense. However, integrating the changes in a dynamic model revealed that purine metabolism globally shifted, in response to malaria, from guanine compounds to adenine, inosine, and hypoxanthine [51]. (3) Data capturing the dynamics of malaria parasites suggested growth rates that were biologically impossible.…”
Section: The Traditional Scientific Method: Hypothesis-driven Deductionmentioning
confidence: 99%